Risk evaluation and mitigation strategy programs in solid organ transplantation: the promises of information technology. (26th February 2014) - Tsapepas, Demetra S; McKeen, Jaclyn T; Martin, Spencer T; Walker-McDermott, Jennifer K; Yang, Alex; Hirsch, Jamie; Mohan, Sumit; Tiwari, Ruchi
Abstract: Risk evaluation and mitigation strategies (REMS) required by the Food and Drug Administration are implemented to manage known or potential risks associated with medications and to ensure ongoing safe use throughout the life of a pharmaceutical agent. Healthcare organizations have begun to adopt information technologies with clinical decision support (CDS) to ensure safe use of medications. Systems have been expanded and customized to also ensure compliance with regulatory standards. End users who are unfamiliar with particular medication use provisions are at risk of unknowingly inappropriately fulfilling specific components. Institution-specific customization of vendor-provided CDS is useful to enhance provider awareness and ensure compliance with standards. Integration of health information technology systems to fulfill REMS requirements is novel and important to ensure consistency as healthcare standards evolve.